2012
DOI: 10.1155/2012/804924
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and Antioxidative Activities ofCornus officinalisagainst Acetaminophen-Induced Hepatotoxicity in Mice

Abstract: The fruit of Cornus officinalis Sieb. et Zucc. is commonly prescribed in Asian countries as a tonic formula. In this study, the hepatoprotective effect of ethanolic extracts of the fruit of C. officinalis (ECO) was investigated in a mouse model of acetaminophen- (APAP-) induced liver injury. Pretreatment of mice with ECO (100, 250, and 500 mg/kg for 7 days) significantly prevented the APAP (200 mg/kg) induced hepatic damage as indicated by the serum marker enzymes (AST, ALT, and LDH). Parallel to these changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 32 publications
2
47
0
1
Order By: Relevance
“…The increase in ALT is the most intense during the first 12 h (Chanda et al, 1995). Our experimental model of hepatotoxicity induced by 6 g APAP/kg bw demonstrated a significant rise of ALT and AST in the first 24 h. The present study correlates with other studies showing significant increases of ALT and AST values after administration of hepatotoxicants like APAP (Liu et al, 2012;Lee et al, 2012;Anwar et al, 2007).The normalization of the above enzymes activities seen in rats treated with the MO extracts indicates inhibition of liver cell injury and reduction of leakage of these enzymes into the blood. These results suggested that MO extracts reduced the toxicity due to elimination of the toxic products of APAP in rats.…”
Section: Discussionsupporting
confidence: 89%
“…The increase in ALT is the most intense during the first 12 h (Chanda et al, 1995). Our experimental model of hepatotoxicity induced by 6 g APAP/kg bw demonstrated a significant rise of ALT and AST in the first 24 h. The present study correlates with other studies showing significant increases of ALT and AST values after administration of hepatotoxicants like APAP (Liu et al, 2012;Lee et al, 2012;Anwar et al, 2007).The normalization of the above enzymes activities seen in rats treated with the MO extracts indicates inhibition of liver cell injury and reduction of leakage of these enzymes into the blood. These results suggested that MO extracts reduced the toxicity due to elimination of the toxic products of APAP in rats.…”
Section: Discussionsupporting
confidence: 89%
“…Liver toxicity is one of the most common toxicity endpoints measured since most xenobiotics are metabolised via the liver. Aspartate transaminase (AST) and alanine transaminase (ALT) are two such biomarkers associated with liver toxicity (Garg et al 2007;Lee et al 2012;Das et al 2011). …”
Section: Measuring Toxicitymentioning
confidence: 99%
“…N-acetyl-p-benzoquinone imine (NAPQI) which is one of the metabolites of paracetamol after the later undergoes metabolism in the liver through the action of cytochrome P450 monooxygenase (Lee et al, 2012) is highly responsible for the toxic effects of paracetamol to liver (Farghaly and Hussein, 2010). Moreover, Somchit et al also suggested that NAPQI is involved in the formation of protein adducts through its action on DNA, proteins, cellular proteins, which in turn lead to the dysfunction and death of hepatocytes and finally liver necrosis (Somchit et al, 2005).…”
Section: Discussionmentioning
confidence: 99%